Galileo, Newton and all that: if it wasn’t a scientific revolution, what was it? (A manifesto) - Garber, Daniel (Circumscribere International Journal for the History of Science, 2009)
This essay is an exploration of how to conceptualize the so-called scientific revolution. A central figure in this discussion is Thomas Kuhn, whose Structure of Scientific Revolutions has shaped much recent discussion of scientific change in the sixteenth through the eighteenth centuries. It is argued that the simple model of a revolution—an old orthodoxy, followed by a period of instability until it is replaced by a new orthodoxy—does not actually represent how change happened in scientific thought in this crucial period. The essay then suggests a different model for understanding change in the period, the Protestant Reformation. Just as in the Reformation the Catholic Church persisted, so Aristotelian natural philosophy persists through much of the so-called scientific revolution. And just as there were multiple sects of protestants who coexisted with one another, there were many alternatives to the dominant Aristotelianism that coexisted and fought as much with one another as with Aristotelian natural philosophy. Without the master narrative provided by the theme of the scientific revolution, the writing of the history of this period is going to be a very open-ended process.